Using Graphic Memoirs in a Counseling Children and Adolescent Course: A Phenomenological Arts-Based Study - Timothy Schoonover; Emily Horton; Kailey Bradley (Teaching and Supervision in Counseling, 2025)
Graphic memoirs in learning environments can facilitate deep educational processes, such as dismantling stigma and biases. There is limited research on the use of graphic memoirs in counselor education. This arts-based phenomenological investigation explored 26 CITs’ experiences with a graphic memoir assignment in a counseling children and adolescent course. There were four themes and one subtheme identified: (a) understanding the Deaf experience and advocacy, (b) professional growth and counseling insights, (c) personal reflection and connection, and (d) educational impact and engagement and one subtheme of using bibliotherapy and creative activities in counseling practice. Discussion and implications for counselor educators are provided.
Keywords: graphic memoirs; arts-based; counselor education; bibliotherapy; creative pedagogy